Longitudinal development of skin involvement and reliability of high frequency ultrasound in systemic sclerosis. Issue 7 (11th June 2004) - Åkesson, A; Hesselstrand, R; Scheja, A; Wildt, M
Abstract : Background: Measurement of skin involvement is essential for diagnosis and prognosis in systemic sclerosis. Assessment by palpation skin score is the current method. Objective: To explore high frequency ultrasound as an objective method to improve skin characterisation by combining measurements of skin thickness and echogenicity. Methods: Skin thickness and echogenicity were measured at the proximal phalanx of the second digit, the back of the hand, the forearm, and the lower leg and, in order to separate limited (lSSc) from diffuse SSc (dSSc), at the chest in 16 patients with early disease and in 16 controls. Measurements were repeated in each patient three or four times with an interval of 1–2 years. Ultrasound measurements of skin thickness were compared with the palpation skin score. Results: Compared with controls, the skin was thickened on the phalanx, hand, forearm, and chest of patients with dSSc, but not patients with lSSc, at the 1 year examination. In dSSc the degree of thickening tended to diminish with time, and at 4 years, thickness was significantly decreased on the forearm and chest compared with the 1 year measurements. Low reflectancy was most pronounced at the 1 year evaluation on the forearm, hand, and phalanx in dSSc, and on the phalanx in lSSc. Conclusion: Separate measurements of skin thickness and echogenicity by high frequency ultrasound add a new dimension to the assessment of skin involvement in SSc, and this seems to be an objective non-invasive tool for use in the study of disease development and in clinical trials.